CORPORATE SOCIAL RESPONSIBILITY: SEBUAH KENISCAYAAN STRATEGI BISNIS DI INDONESIA - Nuzula, Nila Firdausi (IQTISHODUNA, 2009)
There is a new trend that corporation focus not only to maximize wealth for the stockholder and to pursue short term profit but also to maintain its sustainability. CSR as a global business strategy and behavior has been a need for long term corporate sustainability. CSR supports good relationship between corporate and the stakeholders. As a strategy, CSR is a must for developing social capital and for financial and long term non-financial return.